Avaliação dos custos da assistência de recém nascidos de mães diabéticas no Hospital das Clínicas -UNESP – Botucatu - Alcantara, Carolina Amaral de [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The present work had as objective to calculate and to analyze the costs of the assistance of just born of diabetic mothers interned in the units of Joint Lodging of the Maternity and Nursery and UTI Neonatology of the HC - FMB - Unesp. This is a exploratory, descriptive study with quantitative analysis of the data, with just born of carrying mothers of gestational diabetes and of light hyperglycemia, that had carried through the prenatal assistance in the HC - FMB - Unesp, in the period of 1o of January the 31 of December of 2009. The analysis of the data disclosed that the costs indirect and of the assistance to the just born in joint lodging had been of: R$ 160,20 for the group of RN of mothers with light hyperglycemia, R$204,10 for the group with diabetes and R$100,57 for the control. The costs indirect and of the assistance to the just born in Nursery had been of: R$ 494,94 for the group of RN of mothers with light hyperglycemia, R$565,89 for the group with diabetes and R$262,98 for the control. The weighed average cost of the assistance to the just born in Joint Lodging, Nursery and UTI of Neonatology was of: R$ 191,33 for the group of RN of mothers with light hyperglycemia, R$458,58 for the group with diabetes and R$210,48 for the control. It can be concluded that the costs of just born of diabetic mothers and with light hyperglycemia were higher and had similar perinatal results to the one of the control group

O presente trabalho teve como objetivo calcular e analisar os custos da assistência dos recém nascidos de mães diabéticas internados nas unidades de Alojamento Conjunto da Maternidade e Berçário e UTI Neonatologia do HC – FMB -Unesp. Trata-se de um estudo do tipo exploratório, descritivo com análise quantitativa dos dados, sendo com recém nascidos de mães portadoras de diabete, gestacional ou clínico, e de hiperglicemia leve, que realizaram a assistência prenatal no HC – FMB –Unesp, no período de 1o de janeiro a 31 de dezembro de 2009. A análise dos dados revelou que os custos diretos e indiretos da assistência ao recém-nascido em alojamento conjunto foram de: R$ 160,20 para o grupo de RN de mães com hiperglicemia leve, R$204,10 para o grupo com diabete e R$100,57 para o controle. Os custos diretos e indiretos da assistência ao recém-nascido em Berçário foram de: R$ 494,94 para o grupo de RN de mães com hiperglicemia leve, R$565,89 para o grupo com diabete e R$262,98 para o controle. O custo médio ponderado da assistência ao recém-nascido em Alojamento Conjunto, Berçário e UTI de Neonatologia foi de: R$ 191,33 para o grupo de RN de mães com hiperglicemia leve, R$458,58 para o grupo com diabete e R$210,48 para o controle. Pode-se concluir que os custos dos recém nascidos de mães diabéticas e com hiperglicemia leve foram mais elevados e com resultados perinatais similares ao do grupo controle
Keywords: Recém-nascidos – Assistência hospitalar; Museu de Arte do Espírito Santo; Diabetes; Analise de valor (Controle de custo)